2006
DOI: 10.1007/s00024-006-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness Measurements and Acoustic Emission Activity in Brittle Rocks

Abstract: Fracture toughness measurements under static loading conditions have been carried out in Barre and Lac du Bonnet granites. An advanced AE technique has been adopted to monitor real-time crack initiation and propagation around the principal crack in these tests to understand the processes of brittle failure under tension and related characteristics of the resulting fracture process zone. The anisotropy of Mode I fracture toughness has been investigated along specific directions. Microcrack density and orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…The geometry of the microstructure is not the sole parameter controlling the roughness. Other experiments performed using sandstone reported a roughness exponent close to ζ = 0.75 ± 0.03 [21] disagreing with the observation of [17,18]. However, in this work [21] a fracture process zone measured by acoustic emission ahead of the fracture front was actually present while in the latter experiments [17,18] such zone was not existing.…”
Section: Roughness Of the Fracture Wallssupporting
confidence: 80%
“…The geometry of the microstructure is not the sole parameter controlling the roughness. Other experiments performed using sandstone reported a roughness exponent close to ζ = 0.75 ± 0.03 [21] disagreing with the observation of [17,18]. However, in this work [21] a fracture process zone measured by acoustic emission ahead of the fracture front was actually present while in the latter experiments [17,18] such zone was not existing.…”
Section: Roughness Of the Fracture Wallssupporting
confidence: 80%
“…This is evidenced by many field observations of dykes, veins, and joints and field and laboratory experiments on man-made hydraulic fractures in petroleum engineering. Layering in solid materials in general is known to have strong effects on fracture propagation (e.g., Daniel and Ishai, 1994;Broberg, 1999;Brooks and Choudhury, 2002;Nasseri et al, 2006;Zhang et al, 2007;Tvergaard and Hutchinson, 2008). In the following section we explore hydrofracture emplacement in mechanically layered rocks in detail.…”
Section: Hydrofracture Tip Stressesmentioning
confidence: 99%
“…The size of the FPZ and pre-critical stable crack growth are the key factors affecting the fracture toughness. Nasseri et al (2006) measured the fracture toughness and acoustic emission activity in brittle rocks. They found that the variation of fracture toughness is caused by the pre-existing microcrack density and its orientation with respect to the fracture propagation direction.…”
Section: List Of Symbolsmentioning
confidence: 99%